STUDI HIDROLISIS ENZIMATIK JERAMI PADI UNTUK PRODUKSI HIDROGEN MENGGUNAKAN CAMPURAN CRUDE SELULASE DARI - Nadiem Anwar, ; Arief Widjaya, ; Sugeng Winardi, (Matematika dan Sains, 2010)
The aims of research are to compare effectifity the mixture of cellulase enzyme crude from Trichoderma reesei and Aspergillus niger with comercial A. Niger cellulase from Fluka Biochemika and study enfluence of enzyme ratio to substrat. Enzyme crude was made by solid fermentation. T. reesei was incubated for 6 days, while A. niger was incubated for 8 days. One unit activity of A. niger cellulase was mixed with two unit activity of T. reesei cellulase. The straw was milled and was sieved 120-140 mesh, then delignificated using NaOH 2% for 6 hours and at themperature of 85 oC. Yield of glucose was analyzed by dinitrosalycilic acid and measured using spectrophotometer at wavelength of 540 nm. Experiment results showed that the mixture of cellulase enzyme crude from T. reesei and A. niger 2 : 1 U/U was similar with commercial A. niger cellulase in case the bigger enzyme used, the bigger glucose resulted, but its ascension became smaller so enzyme efficiency decreased. The mixture of cellulace crude enzyme of T. reesei with A. niger of 2 : 1 U/U, two times more effective in hydrolizing the cellulose of the straw was compared with comercial A. niger cellulase from Fluka Biochemika.oC. Yield of glucose was analyzed by dinitrosalycilic acid and measured using spectrophotometer at wavelength of 540 nm. Experiment results showed that the mixture of cellulase enzyme crude from T. reesei and A. niger 2 : 1 U/U was similar with commercial A. niger cellulase in case the bigger enzyme used, the bigger glucose resulted, but its ascension became smaller so enzyme efficiency decreased. The mixture of cellulace crude enzyme of T. reesei with A. niger of 2 : 1 U/U, two times more effective in hydrolizing the cellulose of the straw was compared with comercial A. niger cellulase from Fluka Biochemika.